Claudia Jones, international thinker - Dunstan, S; Owens, P (Cambridge University Press, 2021)
This article analyses the early international thought of Trinidad-born Marxist journalist Claudia Jones. We focus on a neglected aspect of Jones's intellectual production in the United States: her interrogation of geopolitics in her Weekly Review articles in the early 1940s. We situate Jones in relation to the contemporary popularization of geopolitical thought in this period, reading her alongside another neglected figure in histories of international thought, the African American geopolitical scholar and diplomatic historian Merze Tate. Jones read together the geopolitical, class, racialized, and anticolonial implications of the expanding Nazi empire, positioning her at the forefront of Marxist theoretical innovation in this period. Moving beyond studies of canonical texts and white male thinkers in international intellectual history, we build on black women's intellectual history to center a black working-class woman's popular theorizing of international relations.